Interdependence of moisture, mechanical properties, and hydrophobic treatment of jute fibre-reinforced composite materials. Issue 10 (3rd October 2017) - Ameer, Muhammad Haris; Shaker, Khubab; Ashraf, Munir; Karahan, Mehmet; Nawab, Yasir; Ahmad, Sheraz; Ali Nasir, Muhammad
Abstract: Despite cheap and sustainable in nature, the use of natural fiber composites is limited due to their high moisture absorption, poor fiber–matrix interface, and lack of data on evolution of properties when subjected to environmental factor such as temperature and humidity. The aim of this research is to study the interdependence of moisture regain, hydrophobic treatment, and the mechanical properties of jute fiber-reinforced composite materials. Composite samples made from treated and untreated jute fiber-reinforced composites were exposed to humid environment and their moisture regain, mechanical properties and fiber-matrix interface was tested at given time intervals until four weeks. The composites produced with hydrophobic treated reinforcement showed lesser moisture regain and improvement in the tensile and flexural strengths compared to untreated fabric composite. A clear improvement in fiber-resin interface was observed by scanning electronic microscopy. The dynamic mechanical analysis of treated and untreated composites was conducted in a temperature range 20–140 °C. An increase in the storage modulus of treated composite materials was noted as compared to untreated ones. Furthermore, it was concluded that developed composite loss their mechanical properties linearly with immersion time. However, this aging was slow in treated fabric composites especially hybrid fluorocarbon and fluorocarbon.